2000
DOI: 10.1046/j.1440-1827.2000.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Solitary squamous cell papilloma of the lung in a 40‐year‐old woman with recurrent laryngeal papillomatosis

Abstract: A rare case of recurrent respiratory papillomatosis (RRP) is reported with a review of the literature. A 40-year-old Japanese woman had suffered from RRP since 1 year of age. She developed a pulmonary squamous papilloma with a thin-walled cavity, which was suspected as being lung carcinoma. The trachea and bronchi around the tumor were intact, and no malignant transformation was present. Two types of human papillomavirus, 6 and 16, were detected, both in the laryngeal and pulmonary papillomas by in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…Recurrent respiratory papillomatosis can, however, be protracted by the need for recurrent surgical interventions to avoid airway obstruction and can extend below the vocal cords, sometimes as far as the main stem bronchi; cases of parenchymal lung involvement have been described (recently reviewed by Harada et al [1]). In addition, a number of cases of malignant transformation either at the laryngeal [2,3], bronchial [4], or pulmonary level [5] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent respiratory papillomatosis can, however, be protracted by the need for recurrent surgical interventions to avoid airway obstruction and can extend below the vocal cords, sometimes as far as the main stem bronchi; cases of parenchymal lung involvement have been described (recently reviewed by Harada et al [1]). In addition, a number of cases of malignant transformation either at the laryngeal [2,3], bronchial [4], or pulmonary level [5] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Harada et al reported the association of squamous cell carcinoma in 19 of 40 patients with bronchopulmonary squamous cell papilloma. 1 Inverted Schneiderian papilloma is reported to be related to the human papilloma virus (HPV) infection. Identifi cation and subtyping of HPV in the specimen may predict recurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…3 Inverted Schneiderian papilloma of the lung is sometimes associated with pulmonary squamous cell carcinoma. 1 We report the case of a large pulmonary Schneiderian papilloma causing elevated serum tumor marker levels in a patient without any evidence of lung cancer.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…3,4 The trachea is the most often involved, 4 whereas extension into the distal bronchi, bronchioles, and lung parenchyma is rare-involvement of the lung parenchyma, for example, occurs in fewer than 1%-7% of cases. [4][5][6][7][8][9] Although a literature search found reports of laryngeal papillomas with lung parenchymal involvement, [4][5][6][7][8][9][10][11][12][13][14] there were few reports describing findings of computed tomography (CT) scans of this condition. 9,15,16 In the present report, we offer the results of chest radiography including CT in a case of pulmonary spread of laryngeal papillomatosis after a period of 6 years.…”
Section: Introductionmentioning
confidence: 99%